Hormonal responses to a single session of wholebody vibration exercise in older individuals. Issue 4 (15th April 2008) - Cardinale, M; Soiza, R L; Leiper, J B; Gibson, A; Primrose, W R
Abstract : Objective: Whole-body vibration (WBV) has been recently suggested as an alternative form of exercise. In this study, the acute effects of a single session of WBV exercise on anabolic hormones in aged individuals were analysed. Design: A randomised cross-over trial design was used. Settings: Geriatrics Department, Woodend Hospital. Participants: 20 individuals (9 men and 11 women; median age 70 years (range 66 to 85 years) volunteered in the experiment. Interventions: Isometric squat on a platform with vibration or no vibration (control) conditions. Main outcome measurements: Plasma cortisol, testosterone, growth hormone (GH) and insulin-like growth factor 1 (IGF-1) were measured before, immediately after, and 1 and 2 h after the interventions. Reports: A significant difference between treatments (p<0.001) and a time6treatment interaction (p<0.05) was found in IGF-1 levels. Cortisol levels were shown not to be significantly different between treatments (p = 0.43), but a difference over time (p<0.001) and a time6 treatment interaction (p<0.05) were identified. No significant differences were identified in GH and testosterone levels. Conclusions: As shown by the results of the study, 5 min of WBV exercise characterised by static squat with a frequency of 30 Hz can be performed by older individuals without apparent signs of stress and/or fatigue. Furthermore, WBV produced an acute increase in the circulating levels IGF-1 and cortisol greater than that observed following the same exercise protocol conducted without vibration.